Kajian terhadap Bobot Badan dan Ukuran Linear Tubuh Induk Kambing Kacang di Lokasi Pengembangan Desa Naas Kecamatan Malaka Barat Kabupaten Malaka - Vinsensia D. Nono; Theresia I. Purwantiningsih; Paulus K. Tahuk (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2021)
This study aims to determine the body weight and linear size of the body of the parent bean goats. This research was conducted in September-December 2020. Located in Naas Village, West Malaka district, Malaka Regency. The livestock used were 15 female goats bean, aged 2-3 years. Determination of livestock age is seen from the number of filed incisors. The method used in this research is the field experiment method with descriptive data analysis. The results showed that the average body weight (kg) of the main goat’s bean observed was 21,62 kg ± 4,45. The average body length (cm) of livestock is 40,93 ± 6,47. The average shoulder height (cm) was 64,30 ± 3,3. The average breast circumference (cm) of the main goat of bean was 65,56 ± 7,30. It can be concluded that the body weight and body linear measurements of the parent goat bean meet the requirements for breeding livestock by the standards of the parent goat in Indonesia.